2022
DOI: 10.1177/01445987211070664
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence mechanism of air leakage on gas extraction in extraction boreholes

Abstract: Borehole leakage is an important cause of gas extraction failure. In order to study the influence mechanism of borehole leakage on gas extraction, the borehole air leakage mode was studied, and a mathematical model was established to describe the borehole air leakage of the gas extraction. In addition, this paper also analyzed the change rules of borehole air leakage and gas extraction effect at different borehole sealing depth, negative extraction pressure, degree of fracture development and borehole sealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…It was found that the crack generation and expansion were mainly driven by tensile stress, and the crack generation pressure increased with the increase in perforation azimuth and confining pressure ratio coefficient. Zhang et al (2022) found that with the improvement of hole sealing quality, the coal rock permeability gradually decreased, the amount of gas leakage from the borehole was significantly reduced, and the gas extraction concentration was significantly increased. Numerous researches on coal seam augmentation and extraction of gas have provided effective technical ideas for the difficult problem of efficient and safe extraction of gas from mines and laid the foundation for the research in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the crack generation and expansion were mainly driven by tensile stress, and the crack generation pressure increased with the increase in perforation azimuth and confining pressure ratio coefficient. Zhang et al (2022) found that with the improvement of hole sealing quality, the coal rock permeability gradually decreased, the amount of gas leakage from the borehole was significantly reduced, and the gas extraction concentration was significantly increased. Numerous researches on coal seam augmentation and extraction of gas have provided effective technical ideas for the difficult problem of efficient and safe extraction of gas from mines and laid the foundation for the research in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The maturity of large-diameter borehole technology makes increasing the diameter of borehole one of the most direct and effective methods to improve gas extraction efficiency, but the increase of borehole diameter will be accompanied by the decrease of borehole stability, which leads to a large number of fissures around the borehole to provide flow channels for gas, thus reducing the efficiency of gas extraction. 10,11 Therefore, the destabilization of boreholes is one of the important factors affecting gas extraction efficiency. When the strain energy gathered around the hole reaches the energy storage limit of the coal and rock body, the large amount of strain energy gathered will be released suddenly, which will eventually show the physical phenomenon of large number of macroscopic fractures around the hole.…”
Section: Introductionmentioning
confidence: 99%
“…Drilling prepumping gas technology can effectively reduce the occurrence of coal mine gas protrusion disaster, and is an important means of coal mine gas management 8,9 . The maturity of large‐diameter borehole technology makes increasing the diameter of borehole one of the most direct and effective methods to improve gas extraction efficiency, but the increase of borehole diameter will be accompanied by the decrease of borehole stability, which leads to a large number of fissures around the borehole to provide flow channels for gas, thus reducing the efficiency of gas extraction 10,11 . Therefore, the destabilization of boreholes is one of the important factors affecting gas extraction efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective way to prevent and control coal or gas outbursts and decrease the probability of their occurrence is gas extraction. Gas extraction using boreholes is the most effective and widely used gas extraction technique, and it can reduce the coal gas pressure and content to reduce the gas outburst danger. However, its overall efficacy in gas extraction is unsatisfactory . In China, the concentration of the drainage holes will attenuate to below 30% after a short gas drainage period in most coal mines. In borehole pressure tests, the rate of effective gas emission of less than 50% will result in an inefficient gas extraction process . The effective way to improve gas extraction efficiency is by improving the performance of sealing materials used in boreholes. …”
Section: Introductionmentioning
confidence: 99%
“… 16 In China, the concentration of the drainage holes will attenuate to below 30% after a short gas drainage period in most coal mines. 17 19 In borehole pressure tests, the rate of effective gas emission of less than 50% will result in an inefficient gas extraction process. 20 The effective way to improve gas extraction efficiency is by improving the performance of sealing materials used in boreholes.…”
Section: Introductionmentioning
confidence: 99%